Factors Affecting to Employee Intention to Leave the Job in Nepalese Commercial Banks - Sony, Suken Kumar; Sah, Puja (Nepalese Journal of Economics, 2025)
This study examines factors affecting to employee intention to leave the job in Nepalese commercial banks. Employee intention to leave is the dependent variable. Similarly, the selected independent variables are work environment, training and development, pay level, job satisfaction and job stress. The study is based on primary data of 18 commercial banks with 170 respondents. To achieve the purpose of the study, the structured questionnaire is prepared. The Kendall’s tau correlation coefficients and regression models are estimated to test the relationship, significance and impact of determinants of factors affecting to employee intention to leave the job in Nepalese commercial banks. The study indicates that work environment has a negative impact on employee intention to leave. This implies that more suitable the working environment, lower would be the employee intention to leave. Likewise, training and development has a negative impact on employee intention to leave. This implies that proper training and developments among the employee decreases the employee intention to leave the job in an organization. Similarly, pay level has a negative impact on employee intention to leave. It indicates that proper pay policy reduces the employee intention to leave the job in Nepalese commercial banks. Similarly, job satisfaction has a negative impact on employee intention to leave, indicating that satisfied employee tends to stay in the bank for a longer time. Likewise, job stress has a positive impact on employee intention to leave which indicates that that higher the job stress, higher would be the employee’s intention to leave job in Nepalese commercial banks.